The Effectiveness of Scaffolding and Storytelling to Improve Reading Comprehension in Descriptive Text - Adi, Mohammad Sofyan (Universitas Nurul Jadid, 2025)
This study aims to examine the effectiveness of the scaffolding and storytelling methods in improving the reading comprehension of descriptive texts among tenth-grade students at SMK Fauzul Hasan. The research was motivated by students' difficulties in understanding the structure and content of descriptive texts. A quantitative approach was used with a pre-experimental one-group pretest-posttest design. Thirty students participated, taking reading comprehension tests before and after the intervention, along with classroom observations. The results showed a significant increase in the average score from 60 to 82, with a large effect size (d = 2.59) and statistical significance (p = 0.0001). Subskill analysis revealed the highest improvement in identifying main ideas (+36%). These findings indicate that the combination of scaffolding and storytelling effectively enhances students' reading comprehension, particularly for low-achieving learners. It is recommended that this method be integrated into the vocational school English curriculum and utilized in teacher training programs to optimize instructional outcomes.